Unravelling conformational and crystal packing preferences of cyclohexane-5-spirohydantoin derivatives incorporating a halogenated benzoyl group. Issue 22 (19th May 2022) - Lazić, Anita; Radovanović, Lidija; Gak Simić, Kristina; Rogan, Jelena; Janjić, Goran; Trišović, Nemanja; Đorđević, Ivana
Abstract : The conformational and supramolecular diversity of spirohydantoins have been investigated. Abstract : Two spirohydantoin derivatives, 3-(4-chlorobenzoyl)-1, 3-diazaspiro[4.5]decane-2, 4-dione (1 ) and 3-(4-bromobenzoyl)-1, 3-diazaspiro[4.5]decane-2, 4-dione (2 ), were synthesized and analyzed by single crystal X-ray diffraction, DFT and QTAIM calculations. Simple substitution of the benzoyl unit gave rise to different crystal structures. In 1, a parallel stack along the b -axis with alternating perpendicular separation is formed, while in 2 the R46(32) nets are joined together to form stacks which enclose linear channels. Hierarchical development of these crystal structures was analyzed through dimeric motifs associated with the presence of intermolecular interactions. By including the previously reported structurally-related spirohydantoin derivatives, we created a set of structures which enabled us to evaluate substituent effects on their conformational preferences, i.e., widening of the dihedral angle between the hydantoin and substituted benzoyl unit when going from F to Br. A conformational search revealed that the value of the torsion angle N3–C11–C12–C13 can be regarded as a compromise between the extended conjugation between the carbonyl and phenyl group and intramolecular C–H⋯O interaction between these two groups. This intramolecular effect is more pronounced on the torsion angle C2–N3–C11–C12, which defines the relative orientation between the hydantoin ring and the carbonyl bridge. The present work may provide a basis for design of new cyclohexane-5-spirohydantoins with potential for pharmaceutical applications both at the molecular and supramolecular level.